Strategi Komunikasi Pelayanan Publik melalui Program Pos Pemberdayaan Keluarga - Ali Alamsyah Kusumadinata; Maria Fitriah (Jurnal Aspikom, 2017)
This research aims to analyze communication strategies of public services through family empowerment program (Posdaya). It uses qualitative descriptive method with interactive analysis techniques to analyze data. Data collection was done by interview, observation and document study. The result shows that communication strategy of public services in the community has improved public service aspects on basic needs of society. Posdaya program is one of the programs as a part of empowerment and that generates basic services to community.